TRANSITION TO MARKET ECONOMY IN THE CENTRAL AND EASTERN EUROPEAN COUNTRIES – COMPARATIVE ANALYSIS - Sikulova, Ivana; Frank, Karol (European Scientific Journal, ESJ, 2014)
While in the Western Europe market economy had developed several centuries, in the Central and Eastern European countries (CEECs) the transition from centrally planned to market economy has been undertaken in a considerably shorter time. Although the long-term objectives of CEECs were similar, discrepancies arose in each country as regards the priorities, order and pace of the reforms to be undertaken. The paper starts with a brief view on the transition process in the CEECs and on the Varieties of Capitalism (VoC) theory. The main part of the paper deals with comparative analysis of economic performance of CEECs’ and three benchmark Western European countries with focus on three dimensions of the economy, namely macroeconomic stability, innovation/growth/competitiveness and welfare/equality. We identify the main differences and similarities across the CEECs from the view of the three dimensions. Then we try to find which out of the two VoC ideal types the respective CEECs are closer to. The key outcomes of the analysis are summarized in conclusion.